Rancang Bangun Sistem Kendali Otomasi Ketinggian Meja Dan Lampu Belajar Sesuai Ergonomi Dan Kesehatan Pengguna - Junianto; Nina Paramytha; Endah Fitriani; Tamsir Ariyadi (Jurnal JEETech, 2024)
Ergonomic challenges are associated with study tables often ignore the user's optimal dimensions and posture. A comfortable study environment is needed to improve productivity and health. It is necessary to design and implement an automatic control system for the table height and study light intensity, utilizing ultrasonic sensors and Light Dependent Resistors (LDR) to adapt to the user's needs. Previous studies often neglect the integration of adjustable furniture with smart lighting systems, causing discomfort and inefficiency in the study environment. A new method is needed by combining a linear DC motor actuator with an L298N motor driver to facilitate table height adjustment between 70 cm and 80 cm, while using a relay module to control the brightness of the lights based on ambient light conditions. The results show that the developed system significantly improves user comfort and health, demonstrating its effectiveness in various settings, including home and workplace. The results show that ergonomic design when paired with automation, can improve user concentration and productivity. This study contributes to the field of ergonomic design by providing a practical solution that addresses table height and lighting, ultimately promoting a healthier and more efficient study environment.